The Caring Relationship of Implementing Nurses to Inpatient Satisfaction in the Internal Lotus Room of Mokopido Tolitoli Hospital: Hubungan Caring Perawat Pelaksana Terhadap Kepuasan Pasien Rawat Inap Di Ruang Teratai Interna RSUD Mokopido Tolitoli - Freny Ravika Mbaloto; Mutmainnah HS; Sova Evie (Salando Health Journal, 2025)
Caring behavior of nurses can provide useful services for patients, caring behavior in the nursing process is very important because this behavior is an important experience for patients during hospital treatment. The purpose of this study is to determine the relationship between the caring behavior of implementing nurses and  the satisfaction of inpatients in the Lotus room of Mokopido Tolitoli Hospital. This study uses a cross sectional design. A sample of 30 patients was selected using a total sampling technique. The research instrument was in the form of a questionnaire on nurses' caring behavior and patient satisfaction levels. Data analysis was carried out using the chi-square test. The results of the analysis showed that most of the nurses showed caring behavior  (80%) and most of the patients were satisfied with the services received (80%). The results of the statistical test showed that there was a significant relationship between the caring behavior of the implementing nurse and patient satisfaction. This is shown by a significant value (p-value) that is smaller than the significance level of 5% (p=0.02). Conclusion: there was a significant relationship between the caring behavior of the implementing nurse and the satisfaction of inpatients in the Lotus room of Mokopido Tolitoli Hospital. Caring behavior  will increase public trust in the implementing nurse in providing nursing care to patients. Therefore, the monitoring and feedback program for nurse caring behavior in the form of periodic patient evaluations needs to be carried out to maintain and increase patient satisfaction.